Ethnicity and drug therapy for hypertension - Amudha, K.; Wong, L.P.; Choy, Anna-Maria J.; Lang, Chim C. (Bentham Science Publishers, 2003)
Physiological and pharmacological responses may be influenced by ethnicity as a result of genetic factors, environmental factors and/or their interaction. This review is divided into 2 parts. Firstly, there will be overview of ethnicity as a determinant of drug metabolism and response with reference to antihypertensive agents. The concept of ethnicity has been applied extensively to the study of hypertension especially in American blacks in whom the hypertension is more common and more aggressive. Thus, the second part of this review will then focus on examining the black-white differences in physiological responses to pharmacological challenge that may provide a link between these models and known ethnic differences in drug responses. We will discuss the hypertension studies that have examined the relative effectiveness of different classes of antihypertensive agents including several recent cardiovascular outcome trials that either have a high proportion of blacks or were conducted entirely in black subjects.